Business Opportunity Of (Nutella Cream Puffs) / Nur Fatimah Othman - Othman, Nur Fatimah (2022)
In this assignment I have decide to sell Nutella cream puffs as my product. For me, in my area there are a good amount of demands of cream puffs. With that I have taken the chance to sell it. Luckily before this I already know on how to make the puffs. For me this is a huge advantage that I have. This business activity took place on May and ended early June. It took one month for me to complete this assignment as it is required.